2021
DOI: 10.1111/cch.12864
|View full text |Cite
|
Sign up to set email alerts
|

‘Their status will be affected by that child’: How masculinity influences father involvement in the education of learners with intellectual disabilities

Abstract: Background Parents play a critical role in the formal education of their children. However, a limited body of scientific knowledge exists on fathers' involvement in the formal education of their children with disabilities, particularly in Global South settings. This study sought to understand how father involvement is constructed in the formal education of learners with intellectual disabilities in an African context. Methods The study uses data from a broad qualitative case study of one special school in Keny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Children with autism have less successful in building positive relationships with their teachers [4]. The main difficulties of children with autism building positive relationships with others are the ability to participate jointly with others, such as they could not paying attention in time to something others paying attention, and children with autism cannot provide quality and quantity interaction, such as raising up too many questions [5].…”
Section: Social Relationship Developmentmentioning
confidence: 99%
“…Children with autism have less successful in building positive relationships with their teachers [4]. The main difficulties of children with autism building positive relationships with others are the ability to participate jointly with others, such as they could not paying attention in time to something others paying attention, and children with autism cannot provide quality and quantity interaction, such as raising up too many questions [5].…”
Section: Social Relationship Developmentmentioning
confidence: 99%
“…These include fathers' attempts to protect their identities as men in societies that associate manliness with being strong and perfect, and disability with being weak and imperfect. Also influencing father involvement are teachers' prejudicial views of men as uncaring and specifically wanting little to do with children with disabilities [2]. Additionally, it has been observed that the fathers' considerations of the benefits of formal education for their children with disabilities influence how they are involved in the education [1].…”
Section: Father Involvement In Education In Kenyamentioning
confidence: 99%
“…The import of father involvement in the life of their children is well documented in the literature. In traditional African communities, fathers mostly take the role of decision making and breadwinning in the family, meaning that their involvement in matters central to the child could lead to enhanced achievement of the child's wellbeing [1,2]. Father-child interactions are associated with the child's improved cognitive, social, language, as well as emotional development [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations